Long-term outcomes of one-stage anterior debridement, bone grafting, and internal fixation for the treatment of lower cervical tuberculosis with kyphosis. (April 2013) - Mao, Ningfang; Shi, Zhicai; Ni, Haijian; Zhao, Yingchuan; Tang, Hao; Liu, Deding; Zhu, Xiaodong; Bai, Yushu; Li, Ming
Abstract Background. Patients with spinal deformities and nerve compression due to spinal tuberculosis often require surgical intervention. The objective of this study was to assess the long-term therapeutic effectiveness of one-stage anterior debridement, bone grafting, and internal fixation for lower cervical tuberculosis with kyphosis. Methods. Twenty-one patients with lower cervical tuberculosis and cervical kyphosis received one-stage anterior debridement, autologous iliac bone grafting, and internal plate fixation. Patients were followed-up postoperatively for at least 5 years. Outcome measures included neck pain using Visual Analogue Scale (VAS) scores, Frankel classification of spinal cord injury, and Cobb angle of cervical kyphosis. Results. Eighteen patients had lesions in 2 vertebrae and 3 had lesions in 3 vertebrae. Cervical tuberculosis was cured in all patients. The mean preoperative VAS score for neck pain was 8 (range: 6–10), whereas the mean best postoperative VAS score was 0.6 (range: 0–3). Mean final VAS score was significantly higher than the best VAS score (2.14 vs. 0.62). Of the 13 patients with symptoms of spinal cord compression, 9 improved by 1 grade and 4 improved by 2 grades according to Frankel classification at final follow-up. The mean preoperative Cobb angle of cervical kyphosis was 29° (range: 15°–50°), whereas the mean postoperative Cobb angle at final follow-up was −1.8° (range: 2–7°). Conclusions. One-stage anterior debridement, bone grafting, and internal fixation can effectively remove lesions, decompress the nerve, reduce pain, and correct kyphosis in patients with cervical tuberculosis and associated kyphosis. Long-term postoperative outcomes were satisfactory.